Nucleocapsid protein gene of Junin arenavirus (cDNA sequence) - Ghiringhelli, Daniel (1989)
The Arenavirus S RNA codes for the major structural polypeptides: the nucleocapsid protein, N, and the glycoproteins Gl and G2, that are derived from an intracellular precursor protein, GPC. We have cloned and sequenced the entire coding region for the N gene of Junin arenavirus, the etiologic agent of Argentine hemorrhagic fever